When inclusion was not an issue: the life story of the first blind lawyer trained in Brazil - Bento Selau; Magda Floriana Damiani (Universidade Federal de Santa Maria (UFSM), 2014)
This work aims to present the findings of an investigation that sought to reconstruct the life story of Walkírio Ughini Bertoldo, considered to be the first blind lawyer to graduate, in Brazil, in 1957. The narrative focuses on the obstacles he faced along the trajectory through this stage of his schooling process, and analyzes the strategies he used to overcome them. The investigative process, which produced Bertoldo´s life story, was guided by the biographical method. Data were collected through interviews with three informants: two college classmates, who later also became his coworkers, and his sister. The research corpus was supplemented by documentary sources related to the subject's life. The findings showed that the trajectory of Bertoldo through higher education was marked by his great dedication and commitment; showed the resistance of the higher education institution to accept blind undergraduates and strategies he used attend the course, in spite of the lack of adapted resources; his intense professional activity, as well as his outstanding contribution to social development and inclusion of the blind in professional and academic life.